IRREGULARITIES IN THE DISPLACEMENT OF THE EARTH’S GEOGRAPHIC POLE AND JERKS IN THE GEOMAGNETIC FIELD - G. S. Kurbasova; A. E. Volvach (Геодинамика и тектонофизика)
There are presented the results of analysis of some irregularities in the series of displacement coordinates on the Earth’s surface for the geographic North Pole in order to relate them temporally to some global jerks in the geomagnetic field. The calculations were made using the International Earth Rotation and Reference Systems Service (IERS) data on the average daily motions of the North Pole from 1962 to 2021 and the information on global jerks in the geomagnetic field measured by the magnetic observatories throughout the world. The identification and analysis of the irregularities in the pole displacement along the Earth’s surface were performed by the Fourier Method and wavelet methods for time series analysis, methods of fixed threshold determination and minimax analysis of the non-Gaussian noise, phase and pseudo-phase space methods, and stroboscopic methods of construction of Poincare maps.The analysis of local Fourier spectra and wavelet-spectra reveals irregularities in the displacement of the North Pole in the time intervals from 1967.04.09 to 1967.11.30, from 1974.03.29 to 1974.09.12, and from 2005.11.03 to 2006.03.07. It is supposed that energy reconstructions which caused short-term pole deviations from the trajectory and starting to follow its previous trajectory at the return points are related to the specific features of oscillatory interactions in the process of the translational-rotational motion of the Earth’s in the Solar System. The time of marking specific points on graphs of the displacement of the pole along the surface of the Earth in 1967 and 1974 is ahead of global geomagnetic jerk occurrence times.